Segregasi Gender dalam Organisasi Spasial Pesantren-Pesantren Besar di Pulau Jawa (Gender Segregation in the Spatial Organization of Large Pesantrens in Java Island ) - Sudradjat, Iwan; Triyoga, Bambang (The ITB Journal Publisher, 2016)
The presence of female santris in big pesantren in Java, which started around 1930, demanded the organization of spatial patterns related to intergender relations in the form of a segregation of activity zones between male and female santris. This study assesses the dynamics of gender segregation in the spatial organization of 18 big pesantren located on Java Island since their establishment until now. The data were collected through field observation, interviews and study of historical documents. The results show that gender segregation in the spatial organization of the pesantren is manifested through the concepts of gender specific zones, territoriality, and boundary. Levels of tolerance and flexibility towards gender segregation are observed within the formal activity zone (madrasah or school), but not in non-formal (boarding houses) and informal (playgrounds, sports, recreation and social activities) zones. Big pesantren in West Java show the highest degree of tolerance towards gender segregation in formal activity zones, followed by big pesantren in Central Java, and lastly by those in East Java. The Kyai as a charismatic leader, policy creator, and decision maker for the interests and benefits of the pesantren, has a significant influence on the level of tolerance of the pesantren as an institution towards gender segregation between male and female santris in the formal activity zone (madrasah or school).